2013
DOI: 10.5935/1676-4285.20134249
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive risks and comprehensive care of pregnant women with hypertensive syndromes: a transversal study

Abstract: Objetivos: Analisar o perfil sociodemográfico e de risco reprodutivo de gestantes com história de síndromes hipertensivas, assim como condições clínicas e obstétricas e características da assistência prestada, durante o pré-natal, parto e pós-parto, em maternidade de alto risco. Método: Estudo transversal, quantitativo, utilizando prontuários de 164 gestantes. Resultados: Predominam mulheres adultas, negras, com escolaridade e renda baixa, multigestas e com múltiplos fatores de risco reprodutivo. Observou-se i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Thereby the strategies offered by the tertiary care under the Family Planning label are not sufficient enough, but, especially the possibility of care in a subject-subject relationship and in a network of references and against references 18 in addition to the planning in a single locus, since even though this is being followed by the woman in the perspective of avoiding the pregnancy, the pregnancy can occur at any time. This is because despite the fact that the directive counseling is appropriate when there is a risk of maternal and fetal death, women present conceptions about the risks different from the conceptions of the professionals who accompany them, besides their reproductive choices are more strongly based on subjective and socioculturally influenced aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby the strategies offered by the tertiary care under the Family Planning label are not sufficient enough, but, especially the possibility of care in a subject-subject relationship and in a network of references and against references 18 in addition to the planning in a single locus, since even though this is being followed by the woman in the perspective of avoiding the pregnancy, the pregnancy can occur at any time. This is because despite the fact that the directive counseling is appropriate when there is a risk of maternal and fetal death, women present conceptions about the risks different from the conceptions of the professionals who accompany them, besides their reproductive choices are more strongly based on subjective and socioculturally influenced aspects.…”
Section: Discussionmentioning
confidence: 99%
“…They overlap and potentiate each other and, along with hypertension, increase the chances of negative outcomes for women and babies 1,9 . Most women present sociodemographic…”
Section: Discussionmentioning
confidence: 99%
“…Studies on healthcare provision to hypertensive pregnant women correlate the inadequacy of prenatal care mainly to professional fault, at the technical or human relations plan 9,16 . Prejudiced and authoritarian practices, with class and gender biases, towards the clinical conditions and reproductive intentions of women in this study were also reported in a study on institutional violence in public maternity hospitals 18 .…”
Section: Comunicação Saúde Educaçãomentioning
confidence: 99%
“…Hypertension, because it is a chronic disease that is closely related to life behaviors, requires periodic clinical care, which is monitored at the basic level and focuses on health education. During pregnancy, however, it entails attendance at all levels of complexity, but with the monitoring of the specialized reference level in order to minimize complications from hypertensive syndrome for the mother and/or fetus (15) . This situation, however, requires the early identification of morbidity at the basic level, which should immediately refer the pregnant woman to the reference unit, at the sign of any reproductive risk factor in prenatal care (1,15) .…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, however, it entails attendance at all levels of complexity, but with the monitoring of the specialized reference level in order to minimize complications from hypertensive syndrome for the mother and/or fetus (15) . This situation, however, requires the early identification of morbidity at the basic level, which should immediately refer the pregnant woman to the reference unit, at the sign of any reproductive risk factor in prenatal care (1,15) . Quality prenatal care presents itself as an important strategy for the detection and early intervention of risk situations, this being a determinant of maternal health indicators.…”
Section: Discussionmentioning
confidence: 99%